"Elisa" Drowning in a River of Tears: Where Does Power Dwell?. Issue 1 (2nd January 2016) - Colzani, Francesca
Abstract : "Elisa" is a treatment report I presented during the 2015 Toronto IARPP Conference, for its discussion in Plenary 3 "Issues of Power and Authority in Relational Psychoanalysis." A woman in her 30s, Elisa seeks treatment during a severe anxiety crisis. A 3-year-long process on a once a week basis is described, focusing in aspects to favor discussion around the plenary subject. Special attention is given to the phenomenological description of the analyst's subjective experience in the process of the co-construction of meaning. Questions about the curative factors involved in this treatment are raised.